Structural features of di(1-adamantyl)benzylphosphane complexes of Cu(I) and Ag(I). (24th November 2016) - Davidson, Ross J.; Ainscough, Eric W.; Brodie, Andrew M.; Freeman, Graham H.; Jameson, Geoffrey B.
Graphical abstract: The sterically congested and basic di(1-adamantyl)benzylphosphane (L), reacts with copper(I) to give 1:1 salts [Cu2 X2 L2 ] (X = Cl, Br, I and SCN) or for copper(I) and silver(I) the 1:2 salts [CuL2 ]BF4 or [AgClL2 ]. Single crystal X-ray studies show the 1:1 salts are dinuclear whereas the 1:2 salts are monomeric. Abstract: The sterically bulky di(1-adamantyl)benzylphosphane (L) reacts with the copper(I) compounds, CuX (X = Cl, Br, I and SCN), in a 1:1 ratio to give the salts CuXL. Single crystal X-ray structures for X = Cl, Br and SCN, show that the complexes exist as dimeric species of the type [Cu2 X2 L2 ] with the X groups bridging to give each copper a distorted trigonal-planar coordination geometry with a 'PX2 ' donor site. When [Cu(CH3 CN)4 ]BF4 reacts with L in a 1:2 ratio, the two-coordinated complex [CuL2 ]BF4 was formed which has a P–Cu–P angle of 169.46(6)°, reflecting the influence of the adamantyl groups. The silver(I) 1:2 compound, [AgClL2 ], has a 'ClP2 ' donor set with a distorted P–Ag–P bond angle of about 149.02(5)°. The reduced coordination numbers, irregular structures and distortions of selected angles are a result of the steric bulk (large cone angle) of L. Some of these structural features may also assist in understanding why Pd(0) complexes of L are effective catalysts for the Sonogashira coupling reactions of arylchlorides and alkynes.